The significance of sensorimotor response components and EMG signals depending on stimuli type in fencing - Borysiuk, Z. (Acta Universitatis Palackianae Olomucensis. Gymnica, 2008)
The purpose of the present study was to examine reaction time, movement time (MT) and electromyography signals under conditions of tactile, acoustic and visual stimulation. Two groups of subjects took part in the study - one consisting of advanced fencers (n = 12, average age 22.3) having practiced fencing for an average of 8.3 years; and the other consisting of novice fencers (n = 15, average age 14.8) having practiced fencing for an average of 2.8 years. The research tool applied in the study was an innovative system of surface electromyography with peripheral equipment that enabled participants` reactions to tactile, audio and visual stimulation to be recorded. The system made it possible to record RT and MT separately. The subjects were exposed to forty five stimuli in a randomized manner for each type of stimulation. The tested fencers responded fastest to tactile stimuli, then to acoustic stimuli, and in a much slower way to visual stimuli (p < 0.01). The advanced fencers exhibited significantly lower values of RT, MT, and EMG in comparison with the novice fencers. Both groups exhibited a decrease in the EMG signal value during the tactile, acoustic and visual stimulation trials, supporting the hypothesis. A slight coincidence of EMG signal curves was also observed in the visual stimuli test. It can be concluded that visual perception lowers muscle tension in novice fencers (p < 0.050).